1993
DOI: 10.1111/j.1464-410x.1993.tb16267.x
|View full text |Cite
|
Sign up to set email alerts
|

p53 Expression and Clinical Outcome in Prostate Cancer

Abstract: Abnormally high levels of expression of p53 protein are found in many human cancers. In most cases increased expression is associated with point mutations in one allele of the p53 gene and loss of the other allele. Accumulation of the protein product can be detected by immunohistochemistry. p53 protein expression in 68 men with prostate cancer, followed up for at least 8 years or until death, was assessed by immunohistochemistry. The aim of the study was to determine the association between p53 protein express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1
1

Year Published

1997
1997
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 11 publications
2
31
1
1
Order By: Relevance
“…In five of seven p53ϩ cases, pathological examination showed extraprostatic extension, and that finding was seen in 10 patients out of 28 of the p53-negative cases (P ϭ .1). Focal cytoplasmic staining was seen in four cases (Patients 3,5,11 and 20) in the Pca and HPIN foci and was counted as negative. Focal (scattered cells) p53 basal staining was seen in about 30% of the cases in the hyperplastic foci but was found very rarely in HPIN foci.…”
Section: Resultsmentioning
confidence: 99%
“…In five of seven p53ϩ cases, pathological examination showed extraprostatic extension, and that finding was seen in 10 patients out of 28 of the p53-negative cases (P ϭ .1). Focal cytoplasmic staining was seen in four cases (Patients 3,5,11 and 20) in the Pca and HPIN foci and was counted as negative. Focal (scattered cells) p53 basal staining was seen in about 30% of the cases in the hyperplastic foci but was found very rarely in HPIN foci.…”
Section: Resultsmentioning
confidence: 99%
“…Expression maintained even in androgenindependent tumors, although it is often amplified or mutated Culig et al 1998;Koivisto et al 1998) p53 Transcription/ apoptotic regulator Mutation rate in is low in primary cancer; frequently mutated in metastasis; p53 overexpression correlated with poor prognosis (Bookstein et al 1993;Effert et al 1993;Navone et al 1993;Thomas et al 1993;Aprikian et al 1994;Henke et al 1994;Voeller et al 1994;Bauer et al 1995;Eastham et al 1995;Heidenberg et al 1995;Shurbaji et al 1995;Moul et al 1996;Prendergast et al 1996;Matsushima et al 1997;Theodorescu et al 1997;Brewster et al 1999;Stackhouse et al 1999) …”
Section: Androgen Receptor Nuclear Hormone Receptormentioning
confidence: 99%
“…27,30,31 Several other studies have demonstrated that p53 protein expression serves as an adverse prognostic indicator in prostate cancer. 29,32,33 The contribution of p53 protein inactivation to the resistance of prostatic epithelial cells to the effects of androgen deprivation is incompletely understood. In this regard, recent observations indicate that the level of p53 mRNA and protein increases in the regressing rat ventral prostate following castration.…”
Section: Hormone-refractory Prostate Cancermentioning
confidence: 99%